Opportunities and Challenges for New and Peripheral Political Science Communities A Consolidated Discipline? - Ilonszki, Gabriella; Roux, Christophe (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"The volume demonstrates that political science on the European fringes has seized opportunities and shown a remarkable development. On the other hand, perils of deinstitutionalization mainly caused by lack of resources and democratic backsliding may darken the discipline's future. It is a must read for all those interested in political science as a discipline and for policy-makers as well." ⁠-Hans-Dieter Klingemann, Emeritus Professor, Berlin Social Science Centre, Germany "As Gabriel Almond famously noted, political science has always been a discipline divided into a great variety of schools and sects. This volume brings a perspective on this perennial theme which is as fresh as it is fascinating. What this reveals is the essential fragility of the discipline due to its power-challenging foundations - an insight which is of increasing significance for the discipline in all parts of the world." ⁠-Matthew Flinders, Professor of Politics at the University of Sheffield, UK "This volume shows how the autonomous status reached by political science in the analysed countries cannot be guaranteed against persistent threats and significant risks of de-institutionalization. A book that deserves to be read by all those who have at heart both the future of the discipline and the quality of democracy." ⁠-Giliberto Capano, Professor of Political Science and Public Policy, University of Bologna, Italy This open access book offers an updated examination of the institutionalisation of political science in sixteen latecomer or peripheral countries in Europe. Its main theme is how political science as a science of democracy is influenced and how it responds to the challenges of the new millennium. The chapters, built upon a common theoretical framework of institutionalisation, are evidence-based and comparative. Overall, the book diagnoses diversity among the country cases due to their take-off points and varied political and economic trajectories. Gabriella Ilonszki is Professor Emerita of Political Science at Corvinus University Budapest, Hungary. Christophe Roux is Professor of Political Science at the University of Montpellier, France.